Differences in the Effects of Two Combinations of Hold Relax Techniques on Gastrocnemius Muscle Pain Reduction - Ma'rifatu Syafa'ah; Aditya Johan R; M Mudatsir Syatibi (Poltekkes Kemenkes Surakarta, 2023)
Background: Pain in the gastrocnemius muscle is often experienced by garment factory workers due to repetitive standing and walking activities. Combination therapy techniques are an alternative to reduce pain and improve muscle function. This study aims to determine the difference in effectiveness between hold relax exercise with auto myofascial release technique and hold relax exercise with auto stretching in reducing gastrocnemius muscle pain in garment company employees. Methods: This study used a quasi-experimental design with a pre-post test control group. A sample of 40 employees with gastrocnemius muscle pain was selected using purposive sampling and divided into two intervention groups of 20 people each. The first group received hold relax exercise and auto myofascial release technique, while the second group received hold relax exercise and auto stretching. Pain was measured using the Visual Analog Scale (VAS). Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: Statistical testing using an independent t-test yielded a result of p=0.007 (p<0.05), which means that there was a difference between groups I and II, with a mean difference after treatment of 13.27 mm in group I and 3.53 mm in group II. Conclusion: Hold relax exercise with the Auto myofascial release technique is more effective in reducing gastrocnemius muscle pain than Hold relax exercise with Auto stretching in garment company employees.